Comprehensive analysis of the pathogen spectrum and antibiotic resistance profiles in periprosthetic joint infections: a single center retrospective study - Cao, Qianqian; Fan, Panlong; Feng, Jiawei; Cheng, Tianmiao; Wang, Xiaoyang; Cheng, Cheng; Dai, Zhipeng (Frontiers in Surgery, 2025)
ObjectiveThe objective of this study was to preliminarily examine the demographic profiles, the spectrum of pathogenic bacteria, and the antibiotic resistance patterns among patients with periprosthetic joint infection (PJI), while also offering deeper insights into the microbiological characteristics specifically in diabetic patients with PJI.MethodsA retrospective analysis of 278 patients diagnosed with PJI from January 2019 to December 2024 at our institution was performed. Demographic characteristics of the patients, the distribution of pathogenic bacteria, and data on antibiotic resistance were statistically analyzed employing the chi-square test and t-test.ResultsGram-positive cocci comprised 56.6% of all pathogenic bacteria, whereas coagulase-negative staphylococci constituted 28.1% of the total. Throughout the study period, a significant decrease was observed in the proportion of rifampicin-resistant coagulase-negative staphylococci (CoNS), from 27.0% to 10.4%. Similarly, a marked decline was noted in the proportion of gentamicin-resistant Staphylococcus aureus, from 50.0% to 15.4%. Conversely, there was a dramatic increase in the proportion of amoxicillin-clavulanate-resistant gram-negative bacilli, from 23.1% to 64.7%. The incidence of fungal infections was notably higher among diabetic patients with PJI compared to their non-diabetic counterparts.ConclusionThis study demonstrates that the distribution pattern of pathogenic bacteria and their antibiotic resistance profiles among patients with PJI undergoes continuous variation. Moreover, there exist significant differences in the distribution of pathogenic bacteria between those with diabetes and those without diabetes among PJI patients. This serves as a crucial theoretical foundation and empirical support for the rigorous and tailored development of anti-infective treatment strategies for patients with various types of PJI.